2023
DOI: 10.1001/jamapediatrics.2023.0008
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield of Exome Sequencing in Cerebral Palsy and Implications for Genetic Testing Guidelines

Abstract: ImportanceExome sequencing is a first-tier diagnostic test for individuals with neurodevelopmental disorders, including intellectual disability/developmental delay and autism spectrum disorder; however, this recommendation does not include cerebral palsy.ObjectiveTo evaluate if the diagnostic yield of exome or genome sequencing in cerebral palsy is similar to that of other neurodevelopmental disorders.Data SourcesThe study team searched PubMed for studies published between 2013 and 2022 using cerebral palsy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 54 publications
(88 reference statements)
1
19
0
Order By: Relevance
“…Early genomic testing in these patients, irrespective of initial clinical diagnosis, can prevent a diagnostic odyssey, with more than half of individuals for whom data were available undergoing a targeted single gene or gene panel before eventually receiving a diagnosis from exome or genome sequencing . As the article by Gonzalez-Mantilla et al concludes, these data provide sufficient evidence to support the inclusion of genomic sequencing as a first-tier test for individuals with cerebral palsy, regardless of their comorbidities and risk factors.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Early genomic testing in these patients, irrespective of initial clinical diagnosis, can prevent a diagnostic odyssey, with more than half of individuals for whom data were available undergoing a targeted single gene or gene panel before eventually receiving a diagnosis from exome or genome sequencing . As the article by Gonzalez-Mantilla et al concludes, these data provide sufficient evidence to support the inclusion of genomic sequencing as a first-tier test for individuals with cerebral palsy, regardless of their comorbidities and risk factors.…”
mentioning
confidence: 99%
“…However, imaging alone will often not provide an accurate etiological diagnosis and may miss the presence of dual etiologies . The meta-analysis by Gonzalez-Mantilla et al reports on 13 studies totaling 2612 individuals with cerebral palsy and conservatively shows that the diagnostic yield of exome or genome sequencing was 31.1%. This is likely to be an underestimate, as not all studies cast a wider genetic net to look for copy number variation and many did not conduct parent-child trio analysis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The disconnect has greatly contributed to protracted litigation with experts of varying degrees of professional stature espousing completely contradictory opinions. Gonzalez-Mantilla et al have rigorously collated the literature and reported that whole exome sequencing (WES) studies found abnormalities in 31% of CP cases. In an accompanying editorial, Van Eyk et al suggested that WES should be performed for all CP cases.…”
mentioning
confidence: 99%